2021
DOI: 10.1002/eap.2298
|View full text |Cite
|
Sign up to set email alerts
|

Response of lion demography and dynamics to the loss of preferred larger prey

Abstract: Large carnivores are experiencing range contraction and population declines globally. Prey depletion due to illegal offtake is considered a major contributor, but the effects of prey depletion on large carnivore demography are rarely tested. We measured African lion density and tested the factors that affect survival using mark-recapture models fit to six years of data from known individuals in Kafue National Park (KNP), Zambia. KNP is affected by prey depletion, particularly for large herbivores that were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Our findings on snaring rates in GKE lions were even more alarming; 45% of the GKE lions sampled had been snared at some point in their lifetime. To our knowledge, ours is the first study to quantify snare injuries of lions originating from throughout the GKE although others (Midlane et al, 2014;Overton et al, 2017;Schuette et al, 2018;Vinks et al, 2021a) have reported sightings of Kafue lions with non-lethal snare injuries. Schuette et al (2018) recorded 79 incidences of snare-related injuries to large carnivores in the northern Kafue NP (NKNP) "over the past 5 years" (presumably 2013-2018), but did not specify number of incidents per species, nor whether recorded incidents included repeated sightings of the same individuals.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our findings on snaring rates in GKE lions were even more alarming; 45% of the GKE lions sampled had been snared at some point in their lifetime. To our knowledge, ours is the first study to quantify snare injuries of lions originating from throughout the GKE although others (Midlane et al, 2014;Overton et al, 2017;Schuette et al, 2018;Vinks et al, 2021a) have reported sightings of Kafue lions with non-lethal snare injuries. Schuette et al (2018) recorded 79 incidences of snare-related injuries to large carnivores in the northern Kafue NP (NKNP) "over the past 5 years" (presumably 2013-2018), but did not specify number of incidents per species, nor whether recorded incidents included repeated sightings of the same individuals.…”
Section: Discussionmentioning
confidence: 91%
“…Schuette et al (2018) recorded 79 incidences of snare-related injuries to large carnivores in the northern Kafue NP (NKNP) "over the past 5 years" (presumably 2013-2018), but did not specify number of incidents per species, nor whether recorded incidents included repeated sightings of the same individuals. Subsequently, Vinks et al (2021a) reported that 80% (n = 5) of the snare injuries that they encountered in NKNP lions from 2013 to 2018 were young adult (4-5.99 year old) males. Again, while it is possible that snaring in GKE declined after 2012, more recent investigations suggest that poaching increased in the region (Overton et al, 2017;Mkanda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a frequent emphasis on the effects of the presence or absence of predator on prey ( Salo et al, 2010 ), minimal research has addressed how the loss of prey may impact predator ecology and behavior ( Rodewald, Kearns & Shustack, 2011 ; Newsome et al, 2015a ). Availability of prey has decreased for apex predators globally ( Wolf & Ripple, 2016 ; Vinks et al, 2021 ), although prey resources have increased in some areas ( Prange, Gehrt & Wiggers, 2004 ). Simultaneously, human activity has altered scavenging opportunities ( Yirga et al, 2012 ; Fey et al, 2015 ) and increased access to anthropogenic resources ( Newsome et al, 2015a ; Ciucci et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because this type of offtake is unregulated, it is often unsustainable, driving extensive wildlife population declines and disproportionately affecting larger-bodied herbivores (Wilkie & Carpenter, 1999; Fa et al, 2000; Creel et al, 2018; Vinks et al, 2020). Herbivore declines, in turn, are widely thought to be a strong driver of carnivore declines in sub-Saharan Africa (Midlane et al, 2014; Rosenblatt et al, 2016, 2019; Creel et al, 2018; Vinks et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Western Zambia's Greater Kafue Ecosystem, comprising Kafue National Park and surrounding Game Management Areas, has been identified as a potential leopard stronghold, on the basis of historical data (Purchase et al, 2007). Little is known about the current status of leopards in the Greater Kafue Ecosystem, although this system now faces extensive anthropogenic pressures from encroachment (Watson et al, 2014) and illegal offtake (Overton et al, 2017), with effects on the large herbivore and carnivore guilds (Creel et al, 2018; Vinks et al, 2020; Vinks et al, 2021). Specifically, the long-term decline of large-bodied prey species has led to prey base homogenization, niche compression, and increased niche overlap within the large carnivore guild, including of leopards and lions Panthera leo (Creel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%